Restoring TRAIL Induced Apoptosis Using Naturopathy. Hercules Joins Hand with Nature to Triumph Over Lernaean Hydra - Ahmad Farooqi, Ammad; Damiano Gadaleta, Cosmo; Ranieri, Girolamo; Fayyaz, Sundas; Marech, Ilaria (Current Genomics, 2017)
Cancer is a multifaceted disease. Our deepened knowledge about genetic and biological mechanisms of cancer cells presents an opportunity to explore the inter-individual differences in the body’s ability to metabolize and respond to different nutrients. It is becoming progressively more understandable that the deregulation of several signaling pathways and the alterations in apoptotic response are some of the major determinants that underpin carcinogenesis. Tumor necrosis factor-Related Apoptosis-Inducing Ligand (TRAIL)-mediated signaling has gained a remarkable appreciation because of its ability to selectively induce apoptosis in cancer cells leaving normal cells intact. However, technological advances have started to shed light on underlying mechanisms of resistance against TRAILinduced apoptosis in cancer cells. The impairment of TRAIL-mediated apoptosis includes various factors ranging from the loss or down regulation of TRAIL receptors or pro-apoptotic proteins to the up regulation of anti-apoptotic proteins. Intriguingly to mention that there is an ever-increasing number of natural herbal extracts (phytometabolites), which have been explored to date for their potential action in restoring apoptosis TRAIL-mediated in cancer cells. In this review, we will highlight the progress in understanding the mechanisms opted by phenolic compounds in overcoming TRAIL resistance.
Keywords: TRAIL